Sosialisasi Keselamatan Lalu Lintas untuk Anak Usia Dini Berbasis Dana Desa - Islah, Mhd.; Setiawan, Beny; Putra, Agus Alisa; Desrimon, Arfi (Journal of Social and Community Service, 2023)
Community service is a manifestation of academics being present in society, which involves the academic community, namely students, lecturers, alumni and other educational staff. Apart from that, it is also an embodiment of the Tri Dharma of Higher Education, namely service whose implementation cannot be separated from the other two dharmas. The description of the stages of program implementation is as follows: a. Planning stage The planning stage is carried out by forming and equipping a team consisting of 2 lecturers and 5 students. Next, prepare a proposal for activities to be implemented. b. Preparatory Stage The preparatory stage is carried out for two weeks, with a description of the activities as follows: A. Early Age Traffic Safety Technical Guidance. The aim of developing a program is to increase public knowledge about traffic through an educational curriculum. For long-term prospects for road safety. B. Technical Guidance on Knowledge Cultivation and Material Simulation There are 4 benefits of Traffic Education in schools, namely: 1. So that the young generation is consciously able to implement the value system, namely the ethics and culture of safe, polite, safe, orderly and smooth traffic which is realized in everyday life. 2. Can change road user behavior. 3. Reducing traffic violations and accidents. 4. Educators and the public can disseminate traffic information.